2012
DOI: 10.2111/rem-d-10-00124.1
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Fire, Livestock Herbivory Removal, and Weather Variability in Texas Semiarid Savanna

Abstract: We examined how the occurrence and structure of grasses and woody plants changed after 12 yr of a fire season manipulation and removal of livestock herbivores. Applying high intensity fires in the summer preserved the structural integrity of this semiarid live oak (Quercus virginiana Mill.) savanna while decreasing or eliminating numerous problematic plants in the understory and overstory, such as prickly pear cactus (Opuntia spp.), sacahuista (Nolina texana S. Watson), Ashe juniper (Juniperus ashei J. Buchhol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 64 publications
2
30
1
Order By: Relevance
“…Juniperus suffered the greatest mortality and this is consistent with a major drought that occurred in the 1950s where Juniperus also had high mortality (Young, ). Likely due to changes in fire regimes, Juniperus has been encroaching into areas previously dominated by live oak savannas (Taylor et al, ). The 2011–2013 drought and future droughts could serve to prevent the encroachment of Juniperus into areas where it has not been abundant in the past.…”
Section: Discussionmentioning
confidence: 99%
“…Juniperus suffered the greatest mortality and this is consistent with a major drought that occurred in the 1950s where Juniperus also had high mortality (Young, ). Likely due to changes in fire regimes, Juniperus has been encroaching into areas previously dominated by live oak savannas (Taylor et al, ). The 2011–2013 drought and future droughts could serve to prevent the encroachment of Juniperus into areas where it has not been abundant in the past.…”
Section: Discussionmentioning
confidence: 99%
“…Meadow dynamics are now linked to multiple processes. Beaver activity can create or maintain meadows [68][70], and fire helps maintain meadows by eliminating woody plants [71][73]. In absence of a natural fire and beaver activities, meadows gradually decrease in size due to tree and shrub encroachment [71], [72], a process that induces a gradual loss of high-quality foraging patches for bison.…”
Section: Discussionmentioning
confidence: 99%
“…; Taylor et al. ). Studies have indicated that not only current year's precipitation affects biomass production; previous year's precipitation is also a major control of biomass production (Sala et al.…”
Section: Introductionmentioning
confidence: 98%